Open Budgetary Meetings Amid a Pandemic: Assessing Connecticut's Various Pathways to Public Engagement During COVID-19 - Gil, Jodie M.; Wharton, Jonathan L. (The Journal of Civic Information, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.jrn; dept.psc; peer-reviewed

Researching SCSU's Hilton C. Buley Library's New Haven Mayoral Archives - Wharton, Jonathan L.; Gil, Jodie (Connecticut History Review, 2021)
The mayoral archive includes both official and personal documents that can be used for research on various aspects of New Haven's history. Much of the DeStefano collection, for example, has various reports and studies on economic development and school construction projects, which were key to his administration.The Hilton C. Buley Library hosts a growing collection of mayoral papers from four New Haven mayors: Biagio “Ben” DiLieto (1980–90), John Daniels (1990–94), John DeStefano Jr. (1994–2014) and Toni Harp (2014–20). The materials are available to the public by appointment. Many items—including the full DeStefano papers—are available in a digital archive through the Buley Library website or the Connecticut Digital Archive portal. Jackie Toce, librarian and head of technical services at Buley Library, has spent the last seven years leading the digitization efforts for the archive, one of the reasons DeStefano donated the materials to Southern.4 Buley Library will host an exhibition and formal unveiling of the archive in late October 2021, which will run through the end of the year.
0 citations (Crossref) [2023-10-31]
Keywords: dept.jrn; dept.psc; peer-reviewed